Evidence of Troglotrema acutum and Skrjabingylus sp. coinfection in a polecat from Lower Austria - Duscher G. G.; Harl J.; Fuehrer H.-P. (Helminthologia, 2015)
The trematode Troglotrema acutum and nematodes of the genus Skrjabingylus are parasitic helminths infecting nasal sinuses of mustelids. Despite different infection routes of these parasites, their occurrence becomes evident due to their destructive lesions of the bone structure of the head, which appears almost similar in both cases.